Like Priests Set Apart: A Source-Critical Problematization of Circumcision, Religious Othering, and Intermarriage - Tumanan, Perdian (Asosiasi Teolog Indonesia, 2019)
There is no biblical conception that so interferes with public life and invites endless debates and controversies as the theology of election. From a religious studies perspective, the theology of election has created a tremendous, hideous impact on the history of humankind, from colonialization to Shoah to the politics of identity and populism today. Rather than being the doctrine that unites humanity, the concept of election has been regarded as the core cause that creates otherness. This article argues that the ideation of otherness in the theology of election is deeply connected to and cannot be separated from sexuality issues. The notion of circumcision, as the main feature of post-exilic priestly election theology, inevitably constructs the ideal of lineage purity, thus forbidding intermarriage. The unfaithfulness of God’s people during the Judean monarchy era would later be perceived as the main cause for the suffering and traumatic experience of exile. Radical holiness in the form of religious separation from other nations must be observed for the priests to enjoy the continuation of God’s promise in the form of descendants. The continuation of priestly lineages would assure the continuity of the Temple's existence and worship.